PENGARUH KUALITAS PELAYANAN, LOKASI, DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN (Studi kasus pada Konsumen “Warung Kopi Tunjang Cafe and Restaurant” Semarang) - Gadhang Pengenggar; Wahyu Hidayat; Sendhang Nurseto (Universitas Diponegoro, 2016)
gmail.comABSTRACTThis research is motivated by the hight growth rate of Semarang Cafes and Restaurants,respectively Cafe and Restaurant also offers a diverse range of facilities to increase the numberof consumers. This is of course just affects the number of visitors who will visit in Cafe orRestaurant because of the many competitors in Semarang. Cafe and Restaurant serviceproviders have to prepare the best strategy to attract consumers, because with the advent of thenew Cafe and Restaurant, consumers are becoming increasingly have many choices. WarkopTunjang Cafe And Restaurant Semarang is one hit from the impact of the number ofcompetitors in the more advanced, it can be seen from Semarang Tunjang warkop revenue thatfell in the last 2 years, namely 2013 and 2014. The problem in this study factors matter whatwhich affect one's decision to visit Warkop Tunjang Cafe And Restaurant Semarang.Specifically focused on three variables: quality of service, facilities and location. The purposeof this research is to study the influence of three variables in influencing consumer purchasingdecisions Warkop Tunjang Cafe And Restaurant Semarang.This type of research is Explanatory Research. The research sample of 100 respondents.Samples were taken using nonprobability sampling techniques, or accidental sampling method.Data were analyzed qualitatively and quantitatively using a data collection instrument(questionnaire) was previously tested through validity and reliability test. While the results ofthe data analysis is done through the analysis of tables, simple linear regression analysis,multiple linear regression analysis, t test, F test with SPSS.The results showed that the quality of service, location and facilities either partially orsimultaneously significantly influence purchasing decisions. Based on the calculation of dataanalysis through a simple regression test concluded that the quality of service influence onpurchasing decisions, the location influence on purchasing decisions, and facilities influenceon purchasing decisions, as well as through multiple regression test concluded that the qualityof service, location and facilities influence on purchase decisions show results significant